Physicochemical Characteristics of Roub; Traditional Fermented Dairy Product of the Sudan - , Mohamed Osman Mohamed Abdalla; , Safinaz Adil Sir El-Khatem Osman (Archives of Current Research International, 2017)
Aims: This study was conducted to determine the physicochemical characteristics of fermented milk “roub”during the storage period. Methodology: Thirty roub samples were collected (10 samples from each of Khartoum, Khartoum North and Omdurman areas) in sterile polyethylene bags, preserved in sample containers in ice (4°C) and transported to the laboratory for analysis. Physicochemical characteristics [fat, protein, total solids (TS), solids-non-fat (SNF), ash, acidity] were determined at 1, 7, 14 and 20-day intervals. Results: The results showed that area from which samples were collected had a significant effect on all physicochemical characteristics of roub except solids-non-fat and acidity. During the storage period, there was no significant variation in all physicochemical characteristics of samples collected from Khartoum except the protein content, while in samples collected from Khartoum North there was a significant effect of the storage period on the protein and total solids contents only, and in samples collected from Omdurman the storage period significantly affected the protein and ash contents and acidity of roub. Roub samples were good up to the end of the storage period. Conclusion: The significant variation in physicochemical characteristics of the product indicates the differences in the source of milk rather than and/or the processing methods. Therefore, the authorities are encouraged to control this process by implementing legislations or prohibit the manufacture of this product in such prevailing conditions.